Innovative Design of Learning Evaluation Textbooks Based on The Independent Curriculum: An Effort to Optimize The Learning Process - Ahmad Zuhdi; Rasmuin Rasmuin; Yuniar Setyo Marandy; Nuril Nuzulia; Novia Solichah (JTP - Jurnal Teknologi Pendidikan, 2025)
This research aims to develop a learning evaluation textbook based on the Merdeka Curriculum as an effort to support the implementation of the curriculum in the educational environment. The Merdeka Curriculum prioritizes learning that is more flexible, student-centered, and emphasizes competency and character development. Therefore, learning evaluation is not only focused on cognitive aspects, but also on the development of attitudes and skills. The research and development used a model adapted from Borg and Gall. Of the ten development steps, researchers only applied seven development steps. The results of this development show 1) the module specifications consist of a cover, a foreword, table of contents, material, implementation of independent curriculum evaluation, and author's biodata. The results of the material expert research were 82.4% with good qualifications, 84% learning design experts with good qualifications, 84% practitioners with good qualifications. 2) The results of the attractiveness of the textbook, the researcher conducted a post test in class to 30 students with the achievement of a percentage of 85.3% with good qualifications. Data analysis used Paired Samples T Test with SPSS 25 tools and Sig results 0.000 <0.02 then Ho is rejected, meaning that there are differences in learning outcomes from students who have used evaluation textbooks. The results showed that the developed learning evaluation textbook was able to assist students in designing and implementing evaluations in accordance with the principles of the Merdeka Curriculum.